PENGELOLAAN KESEHATAN REPRODUKSI PENGUNGSI PASCA GEMPA DI KABUPATEN LOMBOK TIMUR - Nurhidayati Nurhidayati; Retna Siwi Padmawati; Abdul Wahab (Berita Kedokteran Masyarakat (BKM), 2020)
Background: MISP (minimum initial service package) is a guideline for post-disaster reproductive health services. After the earthquake in East Lombok Regency, reproductive health services, according to the MISP standards, need to be seen. Suppose the condition does not comply with the standard. In that case, it will cause many pregnant and lactating women and infants and toddlers to be threatened with the quality of their health and safety. It will have an impact on increased maternal and infant mortality rates.Purpose: Describe the management of reproductive health in pregnant women, women giving birth / postpartum mothers with newborns among IDP victims of the earthquake disaster in East Lombok Regency.Research Methods: This research is a qualitative study with a case study design. In-depth interviews were conducted with 21 informants consisting of 6 stakeholders from the East Lombok District Health Office, four service providers, nine service recipients, and two cross-sectoral. Secondary data and document studies were also used as data sources.Result: Most informants have never heard of the term MISP, and the management of IDPs' reproductive health after the earthquake was not well organized. The organizational structure for managing the district-level health care program, both during the emergency response and rehabilitation phase, has not yet been formed. However, health workers' types of service activities such as midwives, nurses, and doctors from unaffected puskesmas are still running. These activities include ANC, delivery assistance, high-risk detection, and case referral. Family planning services and contraceptives, and the need for romance tents are not provided. As a result, there was an increase in mothers and neonates' high-risk cases and an increase in pregnant women K1 during the rehabilitation period. Provision of the "Kespro" tent for delivery services, pregnant women, and maternity services is available in collaboration with overseas organizations, but there is only one for the entire district. Apart from limited facilities and logistics and sanitation, officers are also less sensitive to other basic needs.Conclusion: There is a gap between the services provided and the minimum initial service package, which is the standard for reproductive health services in crisis times. Preparation of the local government through the relevant regional apparatus organizations is required to immediately prepare a Disaster Management Plan at all stages, starting from comprehensive mitigation, contingency, emergency response, and rehabilitation plan.